Statehood of Palestine and the Exercise of Jurisdiction by the International Criminal Court with Emphasis on the Decision of the Pre-Trial Chamber - Savalan Mohamadzadeh; SEYED TAHA MOUSAVI MIRKOLAEI; keivan eghbali (پژوهشهای حقوقی)
The occupation of a large part of Palestinian lands and long history of war and killings in parts of the said land have always made the existence of a Palestinian state in international law ambiguous. The decision of 5February 2021 of the PTC regarding the exercise of jurisdiction over the crimes committed by the Israeli authorities in the occupied territories, has led to the necessity of raising the issue again in international law. Granting the status of Non-Member Observer State to Palestine according to G/ A Resolution 67/19 in 2012and Palestine's accession to the Rome statute on2January2015, were among the preparations for issuing the said decision. In this decision, PTC without considering itself bound to assess the situation of Palestine's statehood, considered the Court competent to hear,simply because Palestine is a member state of the statute.The basic question in this article is that in the light of the decision of PTC , what role and position does the statehood of Palestine have in determining the jurisdiction of the court?The following article, with the descriptive-analytical method and library tools, reaches the conclusion that despite the existing doubts about the effective control over the land, granting the status of non-member observer state in the UN to Palestine and joining to Various international organizations have had a significant impact in accepting it as a member state in theICC and consequently in confirming the jurisdiction of the Court; A process that indicates an implicit emphasis on the Constitutive theory of recognition in international law.